PERCEIVED RISK AND INTENTION TO PURCHASE FROM OVERSEAS SELLERS IN SHOPEE: JABODETABEK CONSUMER PERSPECTIVE - Silaban, Daniel; Jaunanda, Meiliana; Ferdinand, Ferry (FEB Universitas Sam Ratulangi Manado, 2020)
Abstract. This study aims to examine the effect of financial risk on purchase intention; effect of product risk on purchase intention; effect of security risk on purchase intention; effect of time risk on purchase intention; effect of delivery risk on purchase intention; and effect of psychology risk on purchase intention. The target population Shopee users who have shown intention to conduct online shopping from foreign sellers. The sampling technique used was purposive sampling. The data was collected through questionnaire and analyzed using Partial Least Squares - Structural Equation (PLS-SEM) approach using SmartPLS program. The results showed that financial risk, product risk, delivery risk and psychological risk have significant impact toward purchase intention. The results also showed that security risk and time risk have no significant impact toward purchase intention.Â Keywords: Financial risk, product risk, security risk, time risk, delivery risk, psychology risk, purchase intentionÂ